Reduksi Risiko Musculoskeletal Disorders pada Proses Packing di Industri Garmen - Dioren Tri Paganta; Efie Indrianti; Elty Sarvia (Jurnal Optimalisasi, 2026)
Musculoskeletal disorders (MSDs) remain one of the major issues in manufacturing industries that still rely on manual work, including the textile and garment sectors. The large-scale packing process is often perceived as a simple activity; however, in practice, it involves non-neutral working postures, manual lifting of heavy loads 16–18 kg, and repetitive movements, which increase the risk of MSDs. This study aims to identify the level of postural risk in the large-scale packing process at PT. HX and to design and implement an ergonomic assistive device as an effort to reduce MSD risks. Postural evaluation was conducted on 14 main activity scenarios using the Rapid Entire Body Assessment (REBA) method. The results showed that 92.86% of activities fell into medium to very high-risk categories, with the highest REBA score reaching 11. Further analysis using fishbone diagrams and the 5 Whys method identified that work methods and facility design were the dominant factors contributing to the high ergonomic risk, particularly due to the use of pallets at low working heights (±14 cm) and the absence of ergonomic assistive devices. Based on these findings, an Ergonomic Adjustable Packing Table was designed and implemented, featuring a height-adjustable mechanism using a pneumatic spring and a roller conveyor system with an inclination of approximately 7°. Post-implementation evaluation indicated that no activities remained in the medium to very high-risk categories (0%), and the maximum REBA score decreased from 11 to 2. The number of work activities was also reduced from 14 to 5 ( 64.3% reduction) due to the elimination of high-risk manual handling tasks. In addition, the cycle time for the packing process decreased significantly from 188.04 seconds to 92.15 seconds (an efficiency improvement of 51.0%). These results demonstrate that an ergonomic approach based on postural improvement and assistive device design is effective in enhancing safety, comfort, and work efficiency in large-scale packing processes.